2018
DOI: 10.1210/jc.2018-00294
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Thyroid Function With Bone Density During Childhood

Abstract: A higher FT4 concentration is associated with lower bone mass at the age of 6 and at the age of 10 years. These data provide insights into the effects of thyroid function on bone physiology during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Both studies were conducted based on an adult population in euthyroid and disease-free states. Veldscholte et al demonstrated no significant association between TSH and BMD (g/cm 2 ) and BMC (g) of the total body without the head in a healthy 6-year-old population, and they also suggested that FT4 is a better indicator of bone turnover [ 13 ]. According to our results, based on the thyroid function of unhealthy patients and sex- and age-matched LSBMD z-scores, TSH showed no direct correlation with BMD as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both studies were conducted based on an adult population in euthyroid and disease-free states. Veldscholte et al demonstrated no significant association between TSH and BMD (g/cm 2 ) and BMC (g) of the total body without the head in a healthy 6-year-old population, and they also suggested that FT4 is a better indicator of bone turnover [ 13 ]. According to our results, based on the thyroid function of unhealthy patients and sex- and age-matched LSBMD z-scores, TSH showed no direct correlation with BMD as well.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferating chondrocytes, bone marrow stromal cells, and osteoblasts are the major sites of TH receptor expression. TH is essential for the coordinated progression of endochondral ossification and cartilage matrix mineralization; however, the underlying mechanism of TH’s interaction with the bone matrix needs to be determined [ 12 , 13 ]. In addition, pediatric reference intervals for TH and TSH differ from the adult range and vary with age during childhood; therefore, the accurate identification of abnormal thyroid function is recommended.…”
Section: Introductionmentioning
confidence: 99%
“…There are many known factors that can interfere with peak bone mineral accretion, which occurs around the age of 12 years in girls and 14 years in boys, including heredity, fractures during childhood, nutrition, exercise, oral contraceptive, and age at menarche [18,26]. During the pubertal period, estradiol has important effects, not only for increasing BMD but also for attenuating bone turnover at the endocortical surface, leading to an increase in cortical thickness [27].…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, most studies on the effects of thyroid hormones on bone have focused on adult patients. In children and young individuals, puberty is an important time for bone acquisition toward the attainment of peak bone mass by the end of skeletal development in the third decade of life [17,18]. Optimal peak bone mass acquisition is a determinant of osteoporosis risk and osteoporotic fracture risk [19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, children with thyrotoxicosis have below-average height and craniosynostosis ( 66 ), and an elevated free T4 serum concentration may associate with low BMD ( 67 ) ( Figure 4 ).…”
Section: Thyroid Dysfunction (Hyperthyroidism and Hypothyroidism) Act...mentioning
confidence: 99%